2015
DOI: 10.1002/lsm.22418
|View full text |Cite
|
Sign up to set email alerts
|

Stone/tissue differentiation for holmium laser lithotripsy using autofluorescence

Abstract: With the lock-in technique, autofluorescence from stones can be detected with only the average excitation power of a green aiming beam overlaid to the Ho:YAG-laser beam (power ≤ 1 mW). Since tissue shows very little autofluorescence when excited with 532 nm, this fluorescence signal enables monitoring of the correct position of the treatment fiber during ureteroscopic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Besides fragmentation and movement of calculi, the fluorescence of human kidney stones was investigated in this study. Interesting approaches in this area were recently introduced that involved fluorescence excitation on kidney stones with the aiming beam of a laser system [24,25]. This enables one to develop a feedback system for the laser device to differentiate hard and soft tissue in front of the fiber tip and finally to avoid accidental laser pulse application to surrounding soft tissue [33].…”
Section: Propulsiomentioning
confidence: 99%
See 1 more Smart Citation
“…Besides fragmentation and movement of calculi, the fluorescence of human kidney stones was investigated in this study. Interesting approaches in this area were recently introduced that involved fluorescence excitation on kidney stones with the aiming beam of a laser system [24,25]. This enables one to develop a feedback system for the laser device to differentiate hard and soft tissue in front of the fiber tip and finally to avoid accidental laser pulse application to surrounding soft tissue [33].…”
Section: Propulsiomentioning
confidence: 99%
“…Small fragments may remain untreated clinically because of insufficient visibility and/or low contrast with the surrounding tissue under white light illumination. Suitable recognition techniques have been proposed and are still under development [23][24][25]. In view of these three clinical challenges, the following investigations on fragmentation and propulsion of artificial stones as well as fluorescence response of human calculi were performed to identify optimisation potential in the procedure of laser lithotripsy.…”
Section: Introductionmentioning
confidence: 99%
“…If the fiber was positioned on urinary stone, the voltage was higher by a factor of 3.8–11: six stone samples gave values of U = (1.5 ± 0.3) V to (4.3 ± 0.2) V (see Fig. ‐ results of in vitro measurement series published in ).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the small number of samples, mostly COM and only two stones containing apatite were measured. Also, the kind and number of calculi investigated in an in vitro study were limited . Greenlight excited stone autofluorescence of all clinically relevant types of kidney stones including uric acid and a cystine stone has been shown in the last years by a few groups.…”
Section: Discussionmentioning
confidence: 99%
“…Autofluorescence of kidney stones after excitation with green light has, for example, been mentioned in a paper on a portable system for the ex vivo analysis of urinary stones using Raman spectroscopy . In vitro measurements with human renal calculi showed that nearly all (39 out of 42) calculi gave a strong fluorescence signal when illuminated with 532 nm laser light (power < 1 mW) . Tissue, in contrast, fluoresced much weaker.…”
Section: Introductionmentioning
confidence: 99%